Impact of impurity mixture gas seeded by supersonic molecular beam injection on edge-localized modes in the HL-2A tokamak. (10th June 2019) - Zhong, W.L.; Zou, X.L.; Feng, B.B.; Xiao, G.L.; Liang, A.S.; Yang, Z.C.; Chen, C.Y.; Gao, J.M.; Cheng, J.; Zhang, Y.P.; Wang, T.B.; Han, M.K.; et al.
Abstract: Impurity seeding experiments in ELMy H-mode plasmas by using supersonic molecular beam injection (SMBI) have been performed in the HL-2A tokamak. Besides pure impurity gas (neon, argon), impurities mixed with the main ion fuelling gas by different ratios were seeded into the plasma. It has been observed that the ELM behavior and plasma confinement are very sensitive to the impurity ratio. For 30% Ne impurity seeding, large ELMs are replaced by high frequency bursts (HFBs), which have higher frequency and smaller amplitude compared to the ELMs and the peak heat load on the divertor plate was considerably reduced. Analyses indicate that HFBs originate from the pedestal region and enhance the pedestal particle transport, resulting in a softened pedestal gradient after SMBI. However, for the pure Ne and Ar SMBI seeding, the ELM frequency is decreased and the plasma confinement is moderately improved. Experimental observations suggest that the impurity mixture gas plays a role in changing the pedestal dynamics and there should be an optimal impurity ratio for efficient heat load control in ELMy H-mode plasmas.